Ethical Guidelines on Jordanian Journalists’ use of Artificial Intelligence in the Production of Media Content: A Field Study (Architecture Image Studies, 2025)
This study aims to explore the ethical guidelines surrounding Jordanian journalists’ use of artificial intelligence (AI) in the production of media content. Employing a descriptive-analytical methodology, the research engaged a sample of 100 journalists representing a range of Jordanian media outlets and specialties. The primary focus was to understand journalists’ perspectives on integrating AI into various journalistic tasks across print, digital, broadcast, and audio platforms. The study offers a concise overview of ethical standards, the principles of AI ethics, and the broader implications of AI integration into journalism. It discusses the potential benefits of AI in enhancing journalistic work, as well as the concerns surrounding “robot journalism” and the replacement of human judgment with automated systems. The study reveals that AI adoption in journalism represents a significant ethical shift, as perceived by Jordanian journalists. Concerns regarding accountability, transparency, misuse of AI in spreading misinformation, bias, and fabricated news were highlighted as critical issues. These findings underscore the necessity of maintaining human oversight as a safeguard for journalistic integrity. Based on the results, the study recommends for increasing institutional and individual awareness of ethical responsibilities in the context of AI integration. Investing in capacity-building and training programs to equip journalists with the necessary skills to ethically and effectively utilize AI tools. Organizing educational workshops aimed at familiarizing journalists with AI technologies and ethical considerations, ultimately helping to reduce human workload while promoting responsible media practices that serve the public interest.